Composition and chemical variability of the triterpene fraction of dichloromethane extracts of cork (Quercus suber L.) - Castola, Vincent; Bighelli, Ange; Rezzi, Serge; Melloni, Giovanni; Gladiali, Serafino; Desjobert, Jean-Marie; Casanova, Joseph (Industrial Crops and Products, 2002)
Dichloromethane extracts were prepared from 38 samples of cork harvested in different locations of Corsica and Sardinia from individual trees of Quercus suber L. Friedelin, 3--hydroxyfriedelan-2-one, betulin, betulinic acid, -sitosterol and sitost-4-en-3-one were identiﬁed and their molar percentages were calculated by 13 C NMR spectroscopy, following a procedure recently developed by our group. The results were submitted to chemometric analysis (k-means and principal component analysis), which allowed three groups to be distinguished with respect to the content of friedelin, betulinic acid and 3--hydroxyfriedelan-2-one.
Keywords: 13C NMR; Chemical variability; Chemometric analysis; Cork; extracts

Composition and chemical variability of the triterpene fraction of dichloromethane extracts of cork (Quercus suber L.) (Industrial Crops and Products, 2002)
Dichloromethane extracts were prepared from 38 samples of cork harvested in different locations of Corsica and Sardinia from individual trees of Quercus suber L. Friedelin, 3--hydroxyfriedelan-2-one, betulin, betulinic acid, -sitosterol and sitost-4-en-3-one were identiﬁed and their molar percentages were calculated by 13 C NMR spectroscopy, following a procedure recently developed by our group. The results were submitted to chemometric analysis (k-means and principal component analysis), which allowed three groups to be distinguished with respect to the content of friedelin, betulinic acid and 3--hydroxyfriedelan-2-one.